Biological and molecular characterisation and crystallisation of infectious bursal disease virus and its major capsid protein : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Turitea, Palmerston North, New Zealand - Chai, Yew Fai (Massey University, 2001)
Infectious bursal disease virus (IBDV) is prevalent in most of the poultry producing areas worldwide and causes severe economic losses resulting not only from clinical disease and mortality, but also from the immunosuppressive effect in subclinically infected flocks. The research on IBDV in this thesis is divided into two main parts. In the first part, studies were carried out on the IBDV inadvertently introduced into New Zealand in 1993. Prior to that date, the country had been free from the virus. IBDV was successfully isolated from seven flocks of subclinically infected and/or seronegative chickens in SPF embryonating eggs, adapted to cell culture and identified by EM, immunocytochemistry and RT-PCR test. To evaluate the efficacy of the serological method used in the screening programme of the IBDV eradication scheme, a study was undertaken to compare three diagnostic methods. The study demonstrated that serological testing is not a reliable method for the detection of IBDV infection in New Zealand broiler flocks because antibodies may not have developed to detectable levels by the time of slaughter. Histological examination of affected bursae allowed the demonstration of IBD-like lesions, but these needed to be differentiated from those caused by other agents. The immunocytochemistry test was able to detect early IBDV infection and provided a rapid, definitive diagnosis. Using the immunocytochemistry test to perform a longitudinal study of IBDV infection in a broiler and a layer farm, results showed the birds were infected as early as 6 to 7 days of age. The prevalence of IBDV infection was estimated to be 55% in the broiler flock. The results showed that the serological test had a sensitivity of 28.57% and a specificity of 73.68% for detecting the New Zealand IBDV strain infection. This indicated that there should be further evaluation of the use of serological testing as the sole method for the detection of IBDV infected farms in the current control scheme. An in-vivo pathogenicity study using IBDV derived from a bursal tissue homogenate and carried out in SPF chickens demonstrated the low virulence of the virus present in New Zealand. Molecular analysis of the hypervariable region of the VP2 gene of two 1BDV isolates obtained in 1997 and 1998 showed they are more closely related to attenuated strains than other strains. In all three phylogenetic analyses, using neighbour joining, parsimony and split decomposition, the NZ isolates are closely related to attenuated strain PBG98 and Cul but split away from Australia 002-73, variant E, classical and very virulent strains. Both results support the hypothesis that an attenuated strain of IBDV was inadvertently introduced into the New Zealand poultry population in 1993. In the second part of this thesis, studies on the structure of the IBDV virion and its major capsid protein were initiated by X-ray crystallography. The purification of IBDV for crystallisation and crystallisation trials are described. Several viral crystals were produced from the trials but only weak diffraction was obtained from these crystals. With the aim of studying the structure of the major capsid protein of IBDV (VP2) and investigating the major antigenic site on this capsid protein, the vp2 gene was cloned and expressed, the protein purified, and preliminary crystallisation trials performed. Recombinant VP2 was successfully expressed from a baculovirus expression system. The purification of the recombinant VP2 was also completed in the study and preliminary crystallisation screens determined several conditions favouring the production of crystals.
Keywords: IBVD infection; Poultry diseases; Molecular virology; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300510 Virology